Languages after Brexit How the UK Speaks to the World (Springer International Publishing, 2018)
This book represents a significant intervention into the debates surrounding Brexit and language policy. It analyses the language capabilities and resources of the United Kingdom in a new, post-referendum climate, in which public hostility towards foreign languages is matched by the necessity of renegotiating and building relationships with the rest of Europe and beyond. The authors scrutinize the availability of key resources in diverse sectors of society including politics, economics, business, science and education, while simultaneously offering practical advice and guidance on how to thrive in the new international environment. This extremely timely edited collection brings together leading researchers from across the field of language policy, and is sure to appeal not only to students and scholars of this subject, but also to practitioners, policy makers and educators. Michael Kelly is Emeritus Professor of French at the University of Southampton, UK. A specialist in modern French culture and society, he is active in developing public policy relating to languages and cultural diversity. He edits the European Journal of Language Policy, while his most recent books focus on languages amidst war and conflict.